Los temblores sentidos en Costa Rica durante: 1973-1983, y su relación con la sismicidad del país - Morales, Luis Diego (2011)
Earthquakes in che metropolitan arca of San José, felt with intensity equal or higher than III (MM) for che period 1973-1983, mere localized by means of a local network of stations and portable seismographs, combined with information talen from international bulletins (ISC, PDE, EDR). The distribution of seismi-city and its relation with morphotectonic units allowed a geografic zonification of the country, and mas found that the main seismic sources were associated with subduction and local faults. The last eme proved lo be the most dangerous seismic source and the borders of the internal basins the ones more potentially risky, as evidenced by the Tilarán (1973) and the Pérez Zelechán (1983) earthquakes. The central pacific coast represents a seismic gap and aleo has a high seismic poten-tial. Seismic sequences of the "swarm" type or precursors, main quake and after-shocks hace been observed in the Central Valley, mainly oriented toman d the volca nic area. The type of seismicity observed for the strong earthquakes in the subI duction zone has been, majo quake and aftershocks. The mean value of the felt earthquakes (I= III) in the metropolitan aren of San José mas 14.7 , Per Yeat, that is, about a monthly earthquake. Pee highest seismic activity (VI - VII) mas felt during April 1983. d.le td violent activity around Golfito (Ms = 7.3). The year 1983 has been the most ac,we of tha wbole period as measured by the energy release and material damages, mainly che arcas of Golfito-Osa ami Pérez Zele-dón. However, landslides due o Tilarán's earthquake (1973) yie1ded the largest number of casualties (23), during the whole period.